CONCEPT UNDERSTANDING OFTHE PROUSTLAW AFTER LEARNING WITH RECITATION METHOD USING LKS ON THE STUDENTS CLASS X.C SMAN 1 PANGKALAN BANTENG ACADEMIC YEARS 2014/2015 - Audelia Holyni Grasina; Karelius (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The purpose of this researchis to describe the understanding of concepts of The Law Of Proust after learning with recitation method using LKS in a Class X.C SMAN 1 Pangkalan Banteng academic years 2014/2015. The pretest the students show that only 17,46% of students who are going to be able to determine the mole on the basis of the index and determine the mass of the elements. 30% of students being able to caculated the mass of substances that react, the substanes left, and the substances which, as well as 16% of students who were able to calculate the mass of the elements that are used to react if a known mass of compounds are formed. There is increase in the understanding of conepts to all students in understanding the concepts of the law comparison remain (The Law of Proust) in understanding the relationship of mole with the index, the mass with the mole and the mass of atoms relative (Ar) as well as caculated the mass of substances that react, the substanes left, and the substances which after learning by using the method of recitation receive aid LKS the understanding of concepts students increased by 93,75% after learning with recitation method receive aid LKS.